Implementasi Manajemen dan Dakwah : Studi Kasus : Pondok Pesantren Bismillah - Fadly Tri Karbie Purba; Rini Sumarni; Nuralizah Zannah; Farhis Setiawan (Jurnal Riset Rumpun Agama dan Filsafat, 2024)
Da'wah is an activity that aims to invite people to the path of truth and guidance from Allah SWT, carried out orally or in writing with the spirit of calling and guiding the people. As an integral part of Islamic teachings, this da'wah requires not only sincerity but also good management so that its implementation is effective, structured, and relevant to the development of the times. In this case, management becomes an important element that includes planning, implementing, and evaluating religious programs. The values ​​contained in this management can be reflected in the Qur'an, such as strategy, trustworthy leadership, and a wise approach, emphasizing the importance of integration between da'wah and management. Management is interpreted as an-nizam or at-tanzim, which is a regulatory system that puts everything in its place. The relationship between management and da'wah is synergistic, where da'wah requires a management program and communication media to reach the community effectively and innovatively. A da'i, in this context, also has a very imaudience’s important role, namely as a manager who must understand the audience's characteristics and design the right da'wah strategy. Therefore, the integration of management in da'wah activities is one of the essential needs in building a systematic and competitive da'wah movement amidst modern social dynamics.